The Relationship of Internalized Weight Bias to Weight Change in Treatment-Seeking Adults with Overweight - Rachel D. Marshall; Kerry S. O’Brien; Janet D. Latner (Obesities)
The present study examined data from a randomized controlled trial exploring whether behavioral weight loss treatment was associated with changes in internalized weight bias. The relationship between internalized weight bias and psychological functioning was also assessed. Participants were 106 men and women with overweight or obesity enrolled in a treatment outcome study using the Lifestyle Balance Program. Participants completed measures of internalized weight bias, anti-fat attitudes, self-esteem, body image concern, depressive symptoms, anxiety, and stress. Variables were assessed at baseline, post-treatment, and six-month follow-up. Weight bias internalization significantly decreased over the course of treatment. Baseline and follow-up internalized weight bias scores predicted change in body weight. Participants reporting the lowest levels of internalized weight bias at baseline lost nearly twice as much weight as participants reporting the highest levels of internalized weight bias. Significant associations were found between internalized weight bias, body image concern, and self-esteem. Findings indicate a relationship between internalized weight bias and weight change during behavioral weight loss treatment, highlighting the importance of assessing baseline levels of internalized weight bias in weight loss treatment studies. Higher internalized weight bias predicted poorer weight loss outcomes, indicating a need for tailored treatment approaches.